A aprendizagem do conceito de número de crianças do Infantil V: interações com o flex memo - Belo, Priscila Alves de Paula (2018)
The present work relates the interaction of students at the age of 5 years old with games provided by the Flex memo to the knowledge of the number concept. Legislation and researches in this area advocates the use of play and interactions, through playful practices, with the use of various manipulative materials and among those the game. This way of acting aims to integrate the different areas of knowledge, as well as to relate the daily actions of the human being that learns, considering their cognitive, social, physical and emotional aspects, that is, their integral development (BRASIL, 1998; BRASIL, 2009). In addition, Lorenzato (2006) afirms that the educational progress of children happen when the teacher elaborates a work that combines and integrates the subjects related to the mental schemes and the concept of number, thus constituting a pre-mathematics through several learning situations. Because of this, it is important that the construction of knowledge occurs in a flexible and enjoyable way, with the use of several resources, relating them to the experiences of the student, among these resources the game. In order to do so, this research had as objective: To analyze the contribution of the interaction with the games of Memory, Secret of the Box and Battle provided by the Flex memo for the development of the concept of number of children of the preschool V. The locus of the research was a school of the municipal network of Fortaleza, located in District IV. This dissertation opted for the qualitative approach, considering that the direct contact with the subjects investigated allowed the interpretation of the studied field; and used for data collection the exploratory field study procedures, seeking to delineate the learning possibilities, the interactions and impressions from the experiences provided by the children of preschool V. The steps developed were: observation of the space and interactions at the classes, followed by the verification of the students' knowledge about the concept of number and mathematical notions through interaction with the Memory, Secret of the Box and Battle, provided by the Flex memo. Given the data and results presented, the children participating in this research had fun and reacted very well to the games provided with the Flex memo, and through the interactions experienced with the Game of Memory, Caixa's Secret and Batalha revealed, with the discussions broadened their knowledge about the concept of number.